FACTORS INFLUENCING THE ATTITUDES OF SECONDARY SCHOOL STUDENTS TOWARDS THE STUDY OF MATHEMATICS. - Olayinka, Adesola Afolayan (IJRDO -JOURNAL OF MATHEMATICS, 2023)
It is a known fact that there exist behavioral difficulties among Mathematics students in Estiwani as a result of unresolved attitudinal issues that either the students are not aware of, or that the issues are not properly dealt with. This work seeks to investigate some factors influencing the attitude of secondary school students toward studying Mathematics in the Manzini region. Five schools consisting of two boys-only, two girls-only, and one mixed school were been carefully selected for the investigation. A total of 200 students and 15 qualified teachers were randomly and actively engaged. A combination of the discrete and continuous data collected through observations and using a well-designed questionnaire was carefully analyzed from their graphical representations. It was found that the majority of the students showed a huge gap in the content knowledge and also presented a clear negative attitude towards Mathematics as a subject. Some of the factors responsible for this worrying pattern, as shown by the analysis include poor background from their primary schools, ineffective teaching methods by their teachers, and lack of motivation by their parents among others. Training programs for teachers particularly on the use of technology and teaching aids to better disseminate the contents and the rewards were also highlighted.